"Outcomes of optical penetrating keratoplasty with the large sized donor for failed therapeutic grafts for infectious keratitis from the tertiary eye care center, South India". Issue 6 (November 2022) - Anitha, Venugopal; Ravindran, Meenakshi; Jacob, Ann Divya; Ghorpade, Aditya; Uduman, Mohammed Sithiq
Purpose: To evaluate the preoperative risk factors, complications, and postoperative outcomes following regraft with the large-sized donor for failed therapeutic grafts. Methods: In this retrospective interventional case series, patients who underwent optical penetrating keratoplasty for failed therapeutic keratoplasty (TPK) from 2010 till 2019 were studied at the Cornea clinic, Tertiary eye care center, with a maximum follow-up period of 3 years within the study period. Demographic patterns, preoperative risk factors, graft survival, visual outcomes, and complications were reviewed from the electronic medical records. Results: A total of 77 eyes of 77 patients underwent optical penetrating keratoplasty, with the mean age of 46.18 ± 12.56 years. The median interval between the two procedures was 10.29 months (IQR: 9.0-15.5) and a mean follow-up of 31.27 months. Non-healing fungal keratitis (n = 48) was the most common indication for TPK. The mean size of the donor used was 10 mm (IOR: 9.5-11 mm). The presence of Peripheral anterior synechiae (p < 0.001) and deep limbal vessels (p = 0.011) showed a significant association with the graft outcomes. Four eyes (5%) developed graft reinfection, one patient (1.2%) underwent evisceration, 28 eyes (39%) had graft rejection; among them, 11 eyes (14.28%) resolved with treatment, and in 17 eyes (22.07%), graft failed. Forty-seven eyes (61%) had secondary glaucoma, of which in 32 eyes (68.08%), intraocular pressure was controlled with anti-glaucoma medications; fifteen eyes (31.19%) needed surgery. The graft's cumulative success rate was 83.1% at six months, 58.4% at one year, and 35.1% at three years. Conclusion: We conclude that despite the high complication rate following optical penetrating keratoplasty for failed therapeutic grafts, the visual and clinical outcomes are satisfactory for such high-risk grafts. Hence, it is imperative to venture surgical intervention to salvage these eyes.